A Simple and Effective Method for Observing Starch in Whole Plant Cells and in Raw and Processed Food Ingredients. (2nd November 2020) - Parker, Mary L.; Ryden, Peter; Wilde, Peter J.; Edwards, Cathrina H.
Abstract: A method is described which uses cyclohexanediaminetetraacetic acid (CDTA) to produce numerous separated whole cells from plant tissue. CDTA chelates divalent cations that cross‐link the pectic polysaccharides of the middle lamella, allowing gentle separation of the cells without harsh physical treatments. These individual cells are ideal for observing starch granules in situ by microscopy without the requirement for fixation, embedding, sectioning, or prior starch extraction. Starch can easily be observed either unstained, or by polarizing optics, or after staining with iodide (I2 /KI). Staining with I2 /KI in combination with polarizing optics gives information on polarizing colors that indicate compositional differences within granules. Examples of the starch complement in developing, mature, and cooked rr wrinkled pea cells, and in banana and potato tissue are shown. The CDTA‐separation method is ideal for the survey of starch mutants and other cell components as it preserves cytoplasmic organization and prevents microbial degradation during storage. Abstract : cyclohexanediaminetetraacetic acid (CDTA) cell separation is a versatile and simple method for the examination of edible plant tissues.